Expression Status and Mutational Analysis of the PTEN and P13K Subunit Genes in Ovarian Granulosa Cell Tumors. Issue 3 (1st March 2009) - Bittinger, Sophie; Alexiadis, Maria; Fuller, Peter J.
Abstract : Granulosa cell tumors (GCT) are a unique subset of ovarian tumors which have a molecular phenotype resembling that of follicle stimulating hormone (FSH)-stimulated pre-ovulatory granulosa cells. FSH acts via its receptor to stimulate signaling pathways including the phosphatidylinositol 3-kinase (PI3K)-AKT pathway. Activation of this pathway occurs in solid tumors, including ovarian epithelial tumors, through mutation of the PI3K subunit genes or inactivation of the tumor suppressor, PTEN. Activation of this pathway would be predicted to be tumorigenic in granulosa cells. Expression of the 2 PI3K subunit genes, PIK3CA, which encodes the catalytic subunit, and PIK3R1, which encodes the regulatory subunit, together with the PTEN gene was determined in a panel of GCT, 2 human GCT-derived cell lines, COV434 and KGN, and normal ovary. Direct sequence analysis was used to screen for mutations. Expression of all 3genes was observed in the GCT without evidence of overexpression for the PI3K subunit genes or loss of expression for PTEN. Sequence analysis of amplicons spanning exons 9and 20, in which greater than 75% of mutations occur in the PIK3CA gene did not identify any missense mutations. Similarly, the previously reported deletions in exons 12 and 13 of the PIK3R1 were not found in the GCT. Three amplicons spanning the entire coding sequence of the PTEN gene were sequenced; neither deletions nor mutations were identified. These findings suggest that activation of PI3K signaling through PI3K/PTEN mutation or altered expression, in contrast to many other types of solid tumor, is not associated with GCT.